Mastery Learning Management Of Mathematics' Probability Concept In Immersion Class (Case Study In SMA Negeri 3 Salatiga) - Ichsan, Nur (2012)
This research is aimed to describe the characteristics of mastery learning management in Mathematics' probability concept in the Immersion class of SMA Negeri 3 Salatiga. The spesific objectives of this research are: 1) to describe the characteristics of mastery learning of Mathematics' probability concept done in the Immersion Class of SMA Negeri 3 Salatiga, 2) to describe the mastery learning performance of Mathemetics' probability concept in the Immersion class of SMS Negeri 3 Salatiga. The type of this research is qualitative descriptive in which it describes a situation or phenomenon the way they are with etnograpy research design. The research location is at SMA Negeri 3 Salatiga. The research instrument is the researcher himself. The data used in this research are primary qualitative data and secondary data. The data sources include informant, events and document. The informants are the principal, vice principal of the curriculum sector, mathematics teacher interviewed students and relevant documents. The techniques used for collecting data are observation, interview and documentation. The data analysis techniques include data reduction, data presentation and conclusion drawing. To get the data validity, data source triangulation method is used . The results show: (1) characteristics of Mathematics' probability concept in SMA Negeri 3 Salatiga are planning in the form of teacher's administrative learning set in the beginning of a semester, mastery learning performance in the form of remedial and enrichment program, positioning teacher as the class manager, using group based learning process, using bilingual books, evaluation of mastery learning done after the remedial or enrichment learning. (2) The output of remedial or enrichment program in the from of students' score is performed well so that all students can achieve mastery of learning with the mastery learning process. (3) The characteristics of mastery learning in Mathematics' probability concept in SMA Negeri 3 Salatiga are the supporting factors such as teacher's freedom in the mastery learning performance, facility in the form of adequate supporting books and good cooperation between the subject teacher and counselling teacher. Whereas, the inhibiting factors are time limitation and students' lack of motivation.